A new Geographical Hydrological Modeling in the Calculation of Infiltration and Runoff: A case Goksu basin - Karaosmanoglu, Fatih; Gunek, Halil (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
Water is of great importance for all living life in nature, especially for human beings. The world has limited underground-surface fresh water resources. Increasing world population and the need for water use of this population in many areas such as drinking, agricultural irrigation, industry, energy production, etc., is also increasing exponentially. This situation; Human and economic pressures on river basins jeopardize the risk of pollution of the basins and the sustainability of the water potentials of the basins. For these reasons, it is very important to determine infiltration and runoff in any river basin. On these issues; from past to present, hydrological formulas and methods have been developed by many authors such as. However, natural factors are not included in these formulas and methods in a holistic manner. In this study; A new geographic hydrological model has been developed with the help of GIS, AHP, RS and Digitization techniques by taking into account natural factors on infiltration and runoff in the Goksu Basin. In the hydrological modeling process developed; In order to determine the effects of each natural criterion on infiltration and runoff, it was digitized and processed in the AHP model program. As a result of the mathematical formula and calculations developed in addition to all these, a total of 407.1 mm infiltration and runoff were calculated. This result was correlated with a total flow height of 429.2 mm in the basin and a successful result of 0.95 was obtained.